Parking Measures In Travel Demand Management - Malić, Adolf; Brčić, Davor; Krasić, Davor (Promet - Traffic&Transportation, 2012)
The ever-increasing use of private cars is a consequence ofthe improving standards of town-residents, availability of passengervehicles and their needs and experiences of the freedomof movement. Traffic planners today are faced with the need tomeet the numerous needs for mobility by town-residents andthe available traffic infrastructure, with the aim of sustainableliving in urban agglomerations. Since one of the basic aims ofthe overall traffic policy is the downsizing of the volume of passengervehicle travelling to an acceptable and tolerable measure,the parking measures and strategies are used more andmore frequently as a means of achieving this goal.This is proved by the applied experiences of the cities in thedeveloped countries, and by the growing number of researchand analyses of the parking policy influence on the traffic regulationin town agglomerations. The first results provide encouragementfor planners and strategists to continue designingstrategies and parking policy measures dependent on the transportdemand management in big cities.